Opportunities for local food suppliers to use locality as a competitive advantage : a mixed survey methods approach - Rikkonen, Pasi; Kotro, Jaana; Koistinen, Laura; Penttilä, Katriina; Kauriinoja, Heli (Taylor & Francis, 2013)
Demand for locally produced food products has increased in Finland in the past few years. It has brought new opportunities for food market actors from primary production to retail selling to invest in increasing their capacity and to promote local food on the market. This paper scrutinises local food in two ways, firstly, consumer preferences on purchasing local food and, secondly as comparison, producers' willingness to invest in the growth of local food production and their obstacles in doing so. The data used were obtained from three separate surveys. According to survey results, consumers would prefer to buy products directly from farmers or via small distributors rather than from large chain stores. In addition, the communication of farm enterprises themselves is seen more reliable than the communication by the food industry or retail. The entrepreneurs saw lack of time to develop the business as their biggest obstacle for growth. Still, they seem to be cautious about employing more workforce which could help in the operative every-day work and, thus, set the entrepreneur free to focus on the strategic issues of developing the business. Just a few stated that they consider themselves growth-oriented enterprises. They emphasised distinct growth opportunities, such as new confirmed market channels, as a requirement before considering expanding the business. Also, especially dairy and meat processing enterprises found the legislative requirements ambiguous. From the consumers’ point of view, however, these results lead to believe that there is substantial growth to be gained from locality for local primary producers and small-scale local food refiners. Furthermore, the consumers’ trust towards the communication of farms has room for improvement and especially the communication of farm enterprises themselves should be given more emphasis.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; business opportunities; corporate responsibility; locality; local food enterprice; lähiruoka; kilpailuetu; yritysvastuu